PENGARUH MINAT DAN PERILAKU BELAJAR TERHADAP PRESTASI BELAJAR PROGRAM KEAHLIAN XI AKUNTANSI DI SMK LABOR BINAAN FKIP UNRI PEKANBARU - Sitompul, Astrina; ', Gusnardi; ', Hendripiedes (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This study purpose to determine the influence of interest and learning behavior on the achievement learning skills program XI Accounting in SMK Labor Binaan FKIP UNRI Pekanbaru. The population in this research were student XI accounting skill program with a total of 82 students and all students subject to research, so this research was a population research. Measurement of data used questionnaire and documentation. Data analysis used was multiple linear regression. The result of research based on multiple linear regression has shown learning interest and learning behavior influence to learning achievement of productive accounting skill program XI accounting SMK Labor Binaan FKIP UNRI Pekanbaru was 0,552. This can be seen from the calculation of R2 (R Square Change). This means that the percentage contribution of the influence learning interest and learning behavior on learning achievement variable was 55,2%. Based on these results suggested that students are expected to increase interest and learning behavior from within students.Keyword: Learning Interest, Learning Behavior, Learning Achievement